2003
DOI: 10.1093/hmg/ddh046
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of a human mRNA splicing defect by the plant cytokinin kinetin

Abstract: The defective splicing of pre-mRNA is a major cause of human disease. Exon skipping is a common result of splice mutations and has been reported in a wide variety of genetic disorders, yet the underlying mechanism is poorly understood. Often, such mutations are incompletely penetrant, and low levels of normal transcript and protein are maintained. Familial dysautonomia (FD) is caused by mutations in IKBKAP, and all cases described to date involve an intron 20 mutation that results in a unique pattern of tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
138
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(146 citation statements)
references
References 37 publications
6
138
1
1
Order By: Relevance
“…With recent decriptions of in vitro agents that can rescue the mRNA IKBKAP splicing defect and enhance levels of functional ELP-1 in FD cell lines [20], pathophysiology-based treatment of this disease may evolve out of future clinical trials. The present findings suggest that plama catechol profiling-in particular the DOPA:DHPG ratio-can provide biomarkers with which to track progression of the disease and effects of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…With recent decriptions of in vitro agents that can rescue the mRNA IKBKAP splicing defect and enhance levels of functional ELP-1 in FD cell lines [20], pathophysiology-based treatment of this disease may evolve out of future clinical trials. The present findings suggest that plama catechol profiling-in particular the DOPA:DHPG ratio-can provide biomarkers with which to track progression of the disease and effects of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…13 In this regard, several drugs have been found to modify splicing in other genetic conditions. [3][4][5][6][7] In a previous exploratory study, we demonstrated that kinetin improved exon 36 inclusion in a minigene model for NF1 mutation c.6724C4T. 9 Here, we evaluated the effect of five different drugs, including kinetin, on 19 different mutations and found that kinetin was able to partially correct aberrant splicing caused by four NF1 splicing mutations (c.910C4T, c.3113G4C, c.6724C4T and c.6791dupA).…”
Section: Discussionmentioning
confidence: 93%
“…First, experimental conditions were set up in NF1 EBV-transformed cell lines to optimize drug treatment in relation to cellular toxicity and drug concentration, on the basis of previous reports [3][4][5][6][7] (Supplementary Figure 1). Cellular toxicity was only observed for EGCG treatment at 50 mg/ml.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations